Penerapan Model Pembelajaran Cooperative Learning Tipe STAD Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV SDN 006 Mukti Jaya Kabupaten Rokan Hilir - Rani Sugiarti; Salman Salman; Sakban Sakban (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The low learning outcomes of grade IV students in IPAS subjects are a problem faced. The use of conventional learning models in IPAS subjects causes students to be passive and have difficulty understanding learning. The purpose of this study is to improve student learning outcomes by using the STAD-type cooperative learning model in IPAS subjects. The research method used in this study is Quantitative Descriptive with a Classroom Action Research (PTK) approach which is carried out in 2 cycles. The results of the research obtained are the learning outcomes of students of Indonesiaku Kaya Budaya material in the IPAS subject in the first cycle by using the STAD-type cooperative learning model, achieving classical completeness of 70% and increasing to 89% in the second cycle. This shows that the use of the STAD-type cooperative learning model to improve student learning outcomes is quite effective.